PENGARUH OPINI AUDIT, PROFITABILITAS, LIKUIDITAS, DAN SOLVABILITAS TERHADAP NILAI PERUSAHAAN (STUDI KASUS PADA PERUSAHAAN FOOD AND BEVERAGE) - Khoirunnisa Cahya Firdarini; Dewi Safaatun (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2022)
This study aims to determine the effect of audit opinion, profitability, liquidity and solvency on firm value on food and beverage companies listed on the Indonesia Stock Exchange in the 2015-2019 period and using sales growth as control variable. Based on purposive sampling method, we have 100 firm years of total sample. Research model was tested using classic assumption test to ensure that the model free form classic assumption problem. Hypotesis testing used is multiple regression analysis. The result show that only liquidity that have significant effect to firm value. Audit opinion, Profitability, Liquidity, Solvency have not significant effect to firm value. This result indicated that stakeloder only focused their attention to ability of firm in short time. This is related to characteristic of food and beverage companies that have fast moving assets.